Implementasi Konseling Realita untuk Meningkatkan Motivasi Belajar Siswa Melalui Perubahan Perilaku Adaptif - Ernestje Marhayen; Silta Tawang; Perianti kallolangi (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2026)
This study aims to analyze the application of reality therapy counseling in improving students’ learning motivation influenced by social and family environmental factors. This research uses a qualitative approach with a literature study method supported by interview data as complementary information. Data were collected through the analysis of relevant scientific literature and supported by interviews with parents to describe students’ daily behavior. The results show that low learning motivation is influenced by an unfavorable social environment and lack of family supervision, leading to behaviors that do not support learning activities, such as poor time management and low engagement in academic tasks. The application of reality therapy using the WDEP technique (wants, doing, evaluation, planning) helps students develop self-awareness, evaluate their behavior, and plan more adaptive actions. The findings indicate that reality therapy contributes positively to improving students’ learning motivation through behavioral change and increased personal responsibility. This study concludes that reality therapy can be used as an alternative approach in helping students overcome learning motivation problems.